SPECT/CT in Musculoskeletal Infections - Thang, Sue Ping; Tong, Aaron Kian Ti; Lam, Winnie Wing Chuen; Ng, David Chee-Eng (Seminars in Musculoskeletal Radiology, 2014)
This article provides a brief overview of the current state of hybrid single-photon emission computed tomography/computer tomography (SPECT/CT) imaging in musculoskeletal infections. SPECT/CT imaging, compared with conventional planar study and SPECT alone, provides improved anatomic localization of infection and more accurate delineation of the extent of infection. This article emphasizes three clinical aspects where SPECT/CT is found to be most useful: differentiating between soft tissue and bone infections, assessing suspected infected sites with underlying structural bone alterations, and defining infective focus when complex anatomy is involved. The accurate assessment of site of infection is vital for selecting the most appropriate therapeutic strategy. Other advantages of SPECT/CT imaging such as reducing the inconvenience of combination planar studies, providing additional CT information, and increasing interobserver agreement are also discussed.
Keywords: SPECT/CT; musculoskeletal; infection